X-ray diffraction structures of some phosphatidylethanolamine lamellar and inverted hexagonal phases. - Harper, P E (2001)
X-ray diffraction is used to solve the low-resolution structures of fully hydrated aqueous dispersions of seven different diacyl phosphatidylethanolamines (PEs) whose hydrocarbon chains have the same effective chain length but whose structures vary widely. Both the lower-temperature, liquid-crystalline lamellar (L(alpha)) and the higher-temperature, inverted hexagonal (H(II)) phase structures are solved, and the resultant internal dimensions (d-spacing, water layer thickness, average lipid length, and headgroup area at the lipid-water interface) of each phase are determined as a function of temperature. The magnitude of the L(alpha) and H(II) phase d-spacings on either side of the L(alpha)/H(II) phase transition temperature (T(h)) depends significantly on the structure of the PE hydrocarbon chains. The L(alpha) phase d-spacings range from 51.2 to 56.4 A, whereas those of the H(II) phase range from 74.9 to 82.7 A. These new results differ from our earlier measurements of these PEs (Lewis et al., Biochemistry, 28:541-548, 1989), which found near constant d-spacings of 52.5 and 77.0-78.0 A for the L(alpha) and H(II) phases, respectively. In both phases, the d-spacings decrease with increasing temperature independent of chain structure, but, in both phases, the rate of decrease in the L(alpha) phase is smaller than that in the H(II) phase. A detailed molecular description of the L(alpha)/H(II) phase transition in these PEs is also presented.